Hypernasality in singing among children with cleft palate: A preliminary study / Sabrina Peter - Sabrina , Peter (2017)
Background. Hypernasality is a common problem encountered by most children with cleft palate velopharyngeal insufficiency/ inadequacy (VPI), despite undergoing satisfactory palate repair with the absence of a fistula. Speech therapy has been advocated to treat hypernasality in these children with no residual VPI, after primary palate repair. Previous studies done among classical singers implied that singing closes the velopharyngeal complex longer and tighter as compared to speaking. Thus, hypernasality reduces. As to date, no studies have been conducted to compare voice production in speaking and singing among children with cleft palate. Objectives. This study aims to document differences of hypernasality among children with cleft palate during speaking and singing and to compare the nasality score ratings by trained as well as untrained listeners. Methods. Twenty participants with cleft palate aged between 7 to 12 years old were randomly selected from the Cleft Lip and Palate Association of Malaysia (CLAPAM) database for this study. Audio recordings were made of these children reading a passage and singing a common local song, both in the Malay Language. The degree of hypernasality was judged through perceptual assessment. Three trained listeners i.e. a speech therapist, a classical singer and a linguistic expert, who are academicians and 2 untrained listeners i.e. a cleft volunteer worker and a national high school teacher assessed the recordings using the Visual Analog Scale (VAS), judging the degree of hypernasality and audible nasal emission. Results. Inter-rater and intra rater reliability was verified using intra-class correlation coefficients (ICC) on hypernasality and audible nasal emission of both task of speaking and singing. Significant reduction of hypernasality were observed during singing as compared to speaking, indicating that when a cleft palate child sings, hypernasality reduces. Conclusions. The act of singing significantly reduces hypernasality. However, future researches are necessary to objectively measure nasality, the octave differences in singing compared to speaking as well as proper visualization of the VP complex during singing among children with cleft palate.